REALITA PENYIMPANGAN TUNANGAN DI MASYARAKAT DITINJAU DARI PERAN ORANG TUA, KUHP DAN UU PERKAWINAN - Wahono Suryo Alam, Dody (Program Studi Hukum Keluarga Islam, 2022)
According to Rahmat Hakim (2000: 47-51), fiancé can be said to be a proposal or khitbah which means a request, which according to custom is a form of statement from one party to another with the intention of entering into a marriage bond. The status of fiancées according to Islamic law is not yet legal husband and wife, therefore it is not allowed to live in the same house let alone have a relationship as husband and wife who are bound in a legal marriage according to Islam and according to state law.This study aims to discuss as well as provide solutions to the reality that occurs in the community related to the actions of the fiancées as if they are considered to have officially become a legal husband and wife, in fact they are still fiancées. In fact, not a few often live in the same house or at least often have relations like husband and wife, resulting in pregnancy before marriage.The definition of marriage according to the essence of Islamic law contained in Marriage Law No. 1 of 1974 is the inner and outer bond of a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on God Almighty. Therefore, in addition to the author wants to provide a solution to the reality of the abuse of this fiancé, the author also hopes that this paper can at least provide effective enlightenment / understanding to the community, especially for the perpetrators of the fiancé in order to distinguish between the understanding of the fiancé.